Challenges of Women's Leadership as Principals in Islamic Education Institutions (IEI): Tantangan Kepemimpinan Perempuan Sebagai Kepala Sekolah di Lembaga Pendidikan Islam (LPI) - Chotimah, Chusnul; Fauji, Imam (Indonesian Journal of Innovation Studies, 2026)
General Background Islamic educational institutions continuously strive to navigate organizational challenges and socio-cultural dynamics. Specific Background Female principals at SD Muhammadiyah 2 Sidoarjo encounter complex institutional barriers during their tenure. Knowledge Gap Existing studies frequently highlight female leadership achievements without fully detailing the specific operational obstacles and structural constraints faced in Islamic schools. Aims This study aims to analyze the primary leadership challenges, examine implemented solutions, and identify strategic opportunities for female school heads. Results Qualitative phenomenological findings reveal that gender stereotypes, socio-cultural barriers, and work-life role imbalances constitute primary obstacles, which are mitigated through collective decision-making, staff motivation, innovative project-based learning, and structured character education. Novelty This research unveils a comprehensive framework connecting multi-layered leadership barriers directly with practical institutional solutions in an Islamic elementary school setting. Implications Strengthening collective governance and digital literacy integration provides actionable models to optimize female leadership and institutional quality across Islamic education networks. Key Findings Highlights Female school heads face gender stereotypes, socio-cultural barriers, and work-life role imbalances. Collective governance, staff incentives, and digital project-based learning resolve organizational communication issues. Overcoming institutional obstacles creates sustainable opportunities for technology integration and character education. Keywords: Female Leadership, Islamic Educational Institutions, Gender Stereotypes, Collective Governance, School Principal